Undeclared Work, Deterrence and Social Norms The Case of Germany - Feld, Lars P.; Larsen, Claus; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
For a long time, it has been the declared aim in many countries to fight tax evasion in all its different manifestations, from undeclared work by cleaners and gardeners in private households to tax evasion in the international capital markets. This study focuses on the phenomenon of undeclared work and the case of Germany, presenting the most comprehensive analysis of tax non-compliance for Germany to date, based on surveys conducted by the Rockwool Foundation. Theoretically, the analysis starts from the standard model of tax evasion as being influenced by the subjectively perceived extent of deterrence, the perceived marginal tax burden and social norms. Evidence is provided on the impact of deterrence and other factors on tax non-compliance, and several descriptive statistics are presented to better illustrate the natrure of undeclared work with regard to industry, region, education and other socio-economic characteristics.
Preface -- 1 Introduction -- 2 Defining and Measuring Undeclared Work -- 3 The Size of the German Shadow Economy and Tax Morale According to Various Methods and Definitions -- 4 Deterrence in Germany: A Primer -- 5 Design of the Survey -- 6 The Incidence of Undeclared Work -- 7 The Extent of Undeclared Work in Germany 2001 - 2007 -- 8 The Impact of Deterrence on Undeclared Work -- 9 The Impact of Tax Policy on Undeclared Work -- 10 The Impact of Social Norms on Undeclared Works -- 11 Conclusions -- 12 Appendix.
Keywords: Economics; Economic policy; Finance; Economics/Management Science; Economic Policy; Public Finance & Economics